Distribution of North Pacific right whales (Eubalaena japonica) as shown by 19th and 20th century whaling catch and sighting records - Clapham , Phillip J.; Good, Caroline; Quinn, Sara E.; Reeves, Randall R.; Scarff, James E.; Brownell Jr., Robert L. (J. Cetacean Res. Manage., 2023)
North Pacific right whales (Eubalaena japonica) were extensively exploited in the 19th century, and their recovery was further retarded (severely so in the eastern population) by illegal Soviet catches in the 20th century, primarily in the 1960s. Monthly plots of right whale sightings and catches from both the 19th and 20th centuries are provided, using data summarised by Scarff (1991, from the whale charts of Matthew Fontaine Maury) and Brownell et al. (2001), respectively. Right whales had an extensive offshore distribution in the 19th century, and were common in areas (such as the Gulf of Alaska and Sea of Japan) where few or no right whales occur today. Seasonal movements of right whales are apparent in the data, although to some extent these reflect survey and whaling effort. That said, these seasonal movements indicate a general northward migration in spring from lower latitudes, and major concentrations above 40°N in summer. Sightings diminished and occurred further south in autumn, and few animals were recorded anywhere in winter. These north-south migratory movements support the hypothesis of two largely discrete populations of right whales in the eastern and western North Pacific. Overall, these analyses confirm that the size and range of the right whale population is now considerably diminished in the North Pacific relative to the situation during the peak period of whaling for this species in the 19th century. For management purposes, new surveys are urgently required to establish the present distribution of this species; existing data suggest that the Bering Sea, the Gulf of Alaska, the Okhotsk Sea, the Kuril Islands and the coast of Kamchatka are the areas with the greatest likelihood of finding right whales today.